Analysis of the Process of Improving Table Tennis Sports Game with Specific Interval Training: The Impact of Interval Training on the Improvement of Table Tennis Sports Game (Journal of Advances and Scholarly Researches in Allied Education, 2019)
One of the most popular sports worldwide is table tennis. Table tennis is now the seventh-largest sport in the world with a history of just over 100 years. It is however unclear whether the game is actually better or worse because of this improvement. A consistent approach to quantification is therefore necessary. Interval training is now an integral part of the training methodology. In general terms, each training is in a different sphere a form of interval training. The intensive periods of work and rest are repeated cyclically, but the true interval training must be observed in its own regularities. Interval training can be defined as a training method, comprising all training methods carried out on the basis of the interval principle, requiring a uniform change in load and rest periods. In this study, the improvements seen include physical games such as ball diameters, the rules of the game, set number and score limits. Moreover, compared to real ping pong The benefits of such improvements are also monitored at olympic matches. The results of the study demonstrate that it is beneficial to continuously improve table tennis.